Social Science education - Siti Inayatul Muharromah; Noor Fatmawati (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
Education is a core thing in the development of human life, as well as social studies education. In the learning process there are directions for achieving learning or commonly referred to as curriculum. In social studies learning, it is expected to be able to form superior, civilized and characterized human resources. Become an educated human resource with broad knowledge. With the curriculum 13, it is certainly able to make it easier for teachers to prepare varied learning and also increase student motivation. An integrated curriculum is certainly able to improve the desired social studies learning process. The results of this study aim to be able to balance the professionalism of teachers and students in achieving social studies learning based on Curriculum 13. With the integrity of an integrated curriculum, it certainly gives results that are able to increase human resources with high social spirit, excellence and character. Keywords: Social studies education, Currikulum 13, Character human resources.